2021
DOI: 10.1029/2020jc016663
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Ocean Responses to Typhoon Malakas (2016) in the Vicinity of Taiwan

Abstract: Five to ten typhoons pass Taiwan each year and often cause substantial losses of life and property. In Taiwan coastal areas, typhoon winds generate upper ocean Ekman transport and trigger coastal upwelling or downwelling, depending on the typhoon track orientation relative to the coastline. The storm wind field can mechanically drive the upper water column away from (toward) the coast, forming a divergence (convergence), which induces local coastal upwelling (downwelling) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Both are not conductive to the growth of phytoplankton. When typhoons pass though the northern SCS, their winds also generate upper ocean Ekman transport and trigger upwelling or downwelling, further enhancing or destroying the two upwelling regions [43] depending on the direction of the typhoon path relative to the coastline [44]. This probably results in increased or decreased Chl-a concentrations, which can be partially attributed to nutrient transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Both are not conductive to the growth of phytoplankton. When typhoons pass though the northern SCS, their winds also generate upper ocean Ekman transport and trigger upwelling or downwelling, further enhancing or destroying the two upwelling regions [43] depending on the direction of the typhoon path relative to the coastline [44]. This probably results in increased or decreased Chl-a concentrations, which can be partially attributed to nutrient transportation.…”
Section: Introductionmentioning
confidence: 99%
“…The Regional Ocean Modeling System, a free‐surface, terrain‐following, primitive‐equation, hydrostatic approximation ocean model with a built‐in Lagrangian tracking module (Shchepetkin & McWilliams, 2005) was used to simulate ocean currents (Bao et al., 2017; Shen et al., 2021) and float trajectories. In the Lagrangian tracking module, a float is treated as a small neutrally buoyant particle.…”
Section: Data and Model Setupmentioning
confidence: 99%
“…Shen, Li, et al. (2021) showed that typhoon Malakas triggered two eddies with different mechanisms along the ECS Kuroshio path, which caused the chlorophyll‐a increase. Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The super typhoon Soudelor in 2015 caused an abnormal reverse intrusion of the Kuroshio branch current due to the break of the potential vorticity barrier on both sides of KC (Lü et al, 2021). Shen, Li, et al (2021) showed that typhoon Malakas triggered two eddies with different mechanisms along the ECS Kuroshio path, which caused the chlorophyll-a increase. Chen et al (2003) pointed out that the cross-shelf upwelling of nutrient-rich KSSW due to buoyancy forcing was responsible for new productivity during typhoon Herb.…”
mentioning
confidence: 99%